2022
DOI: 10.1101/2022.10.14.512299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking the behavioral and neural dynamics of semantic representations through negation

Abstract: Combining words and composing meanings is at the basis of human language. However, how the brain constructs meaning online is not well understood. We develop an approach to address this puzzle that exploits the ubiquitous operation of negation. Although negation has been extensively debated among philosophers, psychologists, logicians, and linguists, the cognitive mechanisms supporting this elementary function remain largely unknown. Here, we track the compositional effects of negation ("not") on scalar adject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 113 publications
2
3
0
Order By: Relevance
“…Thus, the fact that the N400 is enhanced by negation indicates that negative operators render the lexical access of single words more difficult. This interpretation is also well in line with the fMRI, behavioral, and recent MEG-MVPA literature that shows an inhibitive effect of negation (Beltrán et al, 2021;Papeo et al, 2016;Zuanazzi et al, 2022). However, additionally with MVPA, we observed that this inhibition effect on semantic retrieval depends on our semantic relatedness manipulation (i.e., semantic integration processes).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, the fact that the N400 is enhanced by negation indicates that negative operators render the lexical access of single words more difficult. This interpretation is also well in line with the fMRI, behavioral, and recent MEG-MVPA literature that shows an inhibitive effect of negation (Beltrán et al, 2021;Papeo et al, 2016;Zuanazzi et al, 2022). However, additionally with MVPA, we observed that this inhibition effect on semantic retrieval depends on our semantic relatedness manipulation (i.e., semantic integration processes).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it could be the case that the inherent limitation of the univariate ERP analysis restricts prior and current ERP analyses from properly detecting the modulative effect of negation on the semantic N400. Interestingly, our finding also echos a recent MVPA study that investigates the effect of negation on the processing of adjectives using MEG (Zuanazzi et al., 2022). By directly comparing low versus high adjectives as the baseline, with cross‐decoding and DAT together, Zuanazzi and colleagues also reported a modulative role of negation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations